2019
DOI: 10.1152/jn.00456.2018
|View full text |Cite
|
Sign up to set email alerts
|

Modeling diverse responses to filled and outline shapes in macaque V4

Abstract: Visual area V4 is an important midlevel cortical processing stage that subserves object recognition in primates. Studies investigating shape coding in V4 have largely probed neuronal responses with filled shapes, i.e., shapes defined by both a boundary and an interior fill. As a result, we do not know whether form-selective V4 responses are dictated by boundary features alone or if interior fill is also important. We studied 43 V4 neurons in two male macaque monkeys ( Macaca mulatta) with a set of 362 filled s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 71 publications
3
24
0
Order By: Relevance
“…Instead, our results support the hypothesis that the responses of individual V4 neurons are informed by two largely separate and independent computations that inform shape and texture selectivity, respectively. Recent studies suggest that texture selectivity may be based on computing high-order image statistics from the visual image (Freeman et al, 2013;Okazawa et al, 2015), whereas shape selectivity may be based on the structure of larger scale contrast boundaries within the RF (Popovkina et al, 2019). Modeling of neural activity with deep convolutional neural networks (CNNs) may provide additional clues into how the brain builds a complex object recognition system from simple earlier representations (Cadieu et al, 2014;Yamins et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, our results support the hypothesis that the responses of individual V4 neurons are informed by two largely separate and independent computations that inform shape and texture selectivity, respectively. Recent studies suggest that texture selectivity may be based on computing high-order image statistics from the visual image (Freeman et al, 2013;Okazawa et al, 2015), whereas shape selectivity may be based on the structure of larger scale contrast boundaries within the RF (Popovkina et al, 2019). Modeling of neural activity with deep convolutional neural networks (CNNs) may provide additional clues into how the brain builds a complex object recognition system from simple earlier representations (Cadieu et al, 2014;Yamins et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Each unique combination of stimulus and RF position was presented for 5-16 repeats, and spike counts were averaged over the 300 ms stimulus presentation. To estimate fill-outline invariance we used data from the study of Popovkina et al (2019). Filled stimuli were drawn from the same set as described for the previous two studies and outline stimuli were the same except the fill was set to be equivalent to background color and the outline width was set to 2,3, or 4 pixels (0.05-0.1 deg) with thicker outlines for more eccentric RFs.…”
Section: Electrophysiological Datamentioning
confidence: 99%
“…The study of its response to color has been particularly influential. V4 was first characterized as a color area [20] before later studies found selectivity for other visual features (such as orientation [21], curvature [3], shape [17,22,23], depth [24][25][26], and motion [27]; reviewed in [28]). The selectivity for different visual features is spatially clustered within V4.…”
Section: Introductionmentioning
confidence: 99%